Analisis Perbandingan Filter Finite Impulse Response, Infinite Impulse Response, dan Discrete Wavelet Transform pada Kondisi Kelelahan Mental berbasis Sinyal Electroenchephalography - Dwinanda Romolo; Edita Rosana Widasari; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The brain is one of the vital organs owned by living things. The brain will work optimally if it gets enough oxygen from the blood. If not, the work of the brain will decrease and will affect human performance in daily activities. One of the reasons for the decreased supply of oxygen to the brain is fatigue. According to the International Labor Organization in 2013, as many as two million workers experienced work accidents due to fatigue caused by mental factors. One way to find out whether humans experience mental fatigue or not is by recording brain wave signal activity or Electroenchephalography (EEG) and analyzing it. To analyze the EEG signal must use digital filters which are very numerous. This study will analyze the EEG signal using three filters, namely Finite Impulse Response (FIR), Infinite Impulse Response (IIR), and Discrate Wavelet Transform (DWT). Then the filtering results from these three filters will be compared to find which filter has the highest efficiency level by looking at the Signal to Noise Ratio (SNR) value and the resulting computational time. The result is that the FIR filter is the most efficient than the other filters, resulting in an average SNR value of 27.89975 dB. While the average value of the resulting computation time is 0.131 s